Biodiversity Book Product in Improving Critical Thinking - Siburian, Tagonna E. (Gunung Djati Conference Series, 2025)
This study will develop a Sumatra biodiversity non-textbook to improve students' critical thinking and problem-solving skills. This ADDIE-based research and development targets grade X students at SMA Negeri 1 Paranginan. Methods include expert validation sheets, questionnaires, and critical thinking tests. The study found that Sumatra's biodiversity non-textbook is practical and beneficial for boosting students' critical thinking skills. Evaluation results show that the experimental class students' N-gain in critical thinking ability (KBK) is 75.7% (effective).